Literacy and Attitudes: Research among Adults in the City of São Paulo, Brazil - Vera Masagao Ribeiro (Adult Education Research Conference, 2000)
The research includes a quantitative and a qualitative stage. Profiles of groups with higher and lower literacy levels are described and explanatory factors of this condition are suggested. Derived from the results, some adult education guidelines are given.